Use of Modern Technologies for the Production Concept of Cutting Tool body - Kolomý, Štěpán (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2025)
This work focuses on the study of the mechanical properties and microstructure of high-strength maraging steel M300 fabricated using the Selective Laser Melting (SLM) method. In the first phase of the experimental study, the surface roughness, hardness, and dynamic and mechanical properties of the fabricated samples in the as-built state were investigated. In the second phase, the effect of different heat treatment temperatures on the final hardness and microstructure of M300 maraging steel was examined. Specifically, the impact of various aging temperatures on mechanical properties and microstructure was evaluated. Furthermore, the mechanical properties of M300, particularly its compressive yield strength, were studied. The compressive pressure test revealed that the highest yield strength was achieved after solution treatment at 840°C for 1 hour, followed by aging at 500°C for 6 hours. The third phase focused on examining the effect of different cutting conditions and material types on the machinability of M300 maraging steel. The final part of this dissertation involves the design, fabrication, and testing of a milling tool body. The fabricated milling cutter underwent technological tests, and the results were compared with those of a conventionally manufactured milling cutter. The comparison was conducted for face milling, slot machining, and shoulder milling under various cutting conditions and with different machined materials. An additional comparison was made regarding the durability of the inserts used when machining tool steel, with and without flood cooling. Finally, the milling tool body was analyzed using vibrodiagnostics, thermal imaging, and a high-speed camera. In conclusion, it was found that the 3D-printed cutter exhibited a 20 % longer tool life when using flood cooling compared to the conventional cutter.

This work focuses on the study of the mechanical properties and microstructure of high-strength maraging steel M300 fabricated using the Selective Laser Melting (SLM) method. In the first phase of the experimental study, the surface roughness, hardness, and dynamic and mechanical properties of the fabricated samples in the as-built state were investigated. In the second phase, the effect of different heat treatment temperatures on the final hardness and microstructure of M300 maraging steel was examined. Specifically, the impact of various aging temperatures on mechanical properties and microstructure was evaluated. Furthermore, the mechanical properties of M300, particularly its compressive yield strength, were studied. The compressive pressure test revealed that the highest yield strength was achieved after solution treatment at 840°C for 1 hour, followed by aging at 500°C for 6 hours. The third phase focused on examining the effect of different cutting conditions and material types on the machinability of M300 maraging steel. The final part of this dissertation involves the design, fabrication, and testing of a milling tool body. The fabricated milling cutter underwent technological tests, and the results were compared with those of a conventionally manufactured milling cutter. The comparison was conducted for face milling, slot machining, and shoulder milling under various cutting conditions and with different machined materials. An additional comparison was made regarding the durability of the inserts used when machining tool steel, with and without flood cooling. Finally, the milling tool body was analyzed using vibrodiagnostics, thermal imaging, and a high-speed camera. In conclusion, it was found that the 3D-printed cutter exhibited a 20 % longer tool life when using flood cooling compared to the conventional cutter.
Use of Modern Technologies for the Production Concept of Cutting Tool body
Keywords: maraging steel M300; Selective Laser Melting (SLM); milling tool body; additive manufacturing; mechanical properties; microstructure; maraging steel M300; Selective Laser Melting (SLM); milling tool body; additive manufacturing; mechanical properties; microstructure